Novel self-anchored CFRP cable system: Concept and anchorage behavior. (1st May 2021) - Ai, Pengcheng; Feng, Peng; Lin, Hongwei; Zhu, Pengcheng; Ding, Guozhen
Abstract: CFRP cables are promising to be utilized in bridge engineering, but their effective anchorage remains a challenge for engineers. To solve this problem, novel self-anchored CFRP cables with different anchorage configurations were designed and tested, with main variables including the radius, thickness, and slope of the CFRP loop at the anchorages. The results indicate that the mechanical behavior of the self-anchored cables is mainly determined by the thickness and radius of the CFRP loop and by increasing these characteristics, the cable's material strength can be fully exploited. With optimized anchorage configurations, the anchor efficiency of the proposed self-anchor CFRP cable system can reach 95% or larger. Additionally, finite element analysis was conducted, with good agreement between the numerical and experimental results. Finally, the influence of the radius and thickness of the CFRP loop on the anchoring capacity and the nominal anchor efficiency was further discussed based on an orthotropic thick-walled cylinder model.